DIAGNOSIS AND ANALYSIS OF FINANCIAL STABILITY AT THE MICROECONOMIC LEVEL - Mnatsakanyan, Grigor; Sargsyan, Varsenik; Hovhannisyan, Martun (Bulletin of Yerevan University G: Economics, 2020)
Annotation Problems of optimal bankruptcy and process management are typical even for developed countries. Among the issues raised are scientific and practical developments aimed at insolvency prevention, in which the authors attempted to have their contribution. The problem will be exacerbated when the Coronavirus Pandemic has a negative impact on almost all sectors of the economy. This will have, to put it mildly, an impact on the financial stability system of the Republic of Armenia at the micro- and macro-levels. The following article examines the criteria by which an organization’s microeconomic performance affects its insolvency, as well as the characteristics of "typical successful" and "typical bankrupt" organizations for the selected group. In order to identify the problem, 3 approaches were proposed: discrete modeling, internal rating, and assessment of the financial condition of organizations by a combined method.